Suppression of LOX activity enhanced seed vigour and longevity of tobacco (Nicotiana tabacum L.) seeds during storage. Issue 1 (28th September 2018) - Li, Zhan; Gao, Yue; Lin, Cheng; Pan, Ronghui; Ma, Wenguang; Zheng, Yunye; Guan, Yajing; Hu, Jin
Abstract: The preservation of seed viability and quality in storage is an important trait both for commercial and germplasm usage. To better explore potential mechanisms of tobacco seed deterioration, seed packed in cloth bag (C) and vacuum bag (V) were stored under room temperature (RT) and low temperature (LT, 18°C), and sampled periodically for laboratory testing. Seed stored in low temperature with vacuum bag (LT/V) owned the highest seed vigour after 25 months of storage and in room temperature with cloth bag (RT/C) lost seed vigour and germination ability after 20-month storage. Meanwhile, seed in RT/C notably increased about 5-fold endogenous hydrogen peroxide (H2 O2 ), 4-fold malondialdehyde (MDA) contents, 12-fold Lipoxygenases (LOX) activity and 2-fold the expression of NtLOX3 comparing with LT/V at the end of 15-month storage. In addition, regression analysis indicated that LOX activity was strongly negatively correlated with seed vigour as the R 2 value reached 0.970 in RT/C. Furthermore, caffeic acid and catechin, the inhibitors of LOX activity, were applied to tobacco seeds pre-treatment and followed with artificial accelerated aging. Seeds pretreated with inhibitors, especially caffeic acid, reduced LOX activity by 50%, MDA and H2 O2 contents by 40% and 20%, respectively, and increased more than 1.2-fold seed vigour and seedling quality comparing with seeds pretreated with H2 O after 6-day artificial aging, indicating a better seed storability after artificial accelerated aging. These results suggest that LOX accelerated seed aging, and suppression of LOX activity enhanced seed vigour and viability in accelerated aging tobacco seed, opening new opportunities for effective management of seed germplasm under long-term storage and conservation.